Isomers in the phosphine-substituted heteronuclear cluster RuOs(µ-H)₂(CO)₁₂(PPh₃) – a re-examination - Ng, Shi Hoe (2021)
The solution-state isomers of the heteronuclear cluster RuOs3(µ-H)2(CO)12(PPh3) have been re-examined in the light of conflicting structural assignments for a closely-related analogue. The result is a reassignment of the structures and hence the exchange processes observed in the NMR spectra.